The Composition, Size Distribution and Growth Patterns of Penaeus monodon and Penaeus merguiensis at the Estuary of Tukad Aya, Jembrana Bali - Siagian, Josua; Arthana, I Wayan; Pebriani, Dewa Ayu Angga; Saraswati, Suprabadevi Ayumayasari (Advances in Tropical Biodiversity and Environmental Sciences, 2020)
Estuary ecosystem has an important role in supporting the life of shrimp. High productivity and the availability of natural food in the estuary ecosystem, will indirectly affect the growth of shrimp. Penaeus monodon and Penaeus merguiensis were two species of shrimp that had economic value with high demand. The purpose of this study was to determine the biological aspects of Penaeus monodon and Penaeus merguiensis shrimp at estuary of Tukad Aya, Bali. Data collection was carried out in February-March 2019 using quantitative descriptive research methods. The determination of the research station was done by purposive sampling. The results showed the total number of shrimps were caught 1,756 individuals, which consist of Penaeus monodon 151 individuals, Penaeus merguiensis 224 individuals and 1,325 individuals of other shrimp. The composition of Penaeus monodon (8.6%) was less than Penaeus merguiensis (12.76%). Shrimp length measurements were divided into 9 groups with a range of values of 55.15-189.95 mm in Penaeus monodon and 31.3-140.1 mm in Penaeus merguiensis . The results of the length and the weight regression in both species of shrimp obtained the value of b <3 so that the growth pattern of shrimp was categorized as negative allometric where length growth was faster than weight gain.